How to Build a Customized Scoring Tool to Evaluate and Select Early-stage Projects: Companies can design a customized multi-factor scoring tool for early-stage projects to make the decision-making process as consistent and objective as possible. Issue 3 (4th May 2022) - Mitchell, Rick; Phaal, Rob; Athanassopoulou, Nikoletta; Farrukh, Clare; Rassmussen, Christian
Overview: In the early stages of technology or innovation projects, companies often need to make decisions about which projects to pursue when only scant information is available. In this article, we provide guidance on how to make the best use of the information available by assessing projects against several appropriate factors and allocating scores. Although companies have used this type of scoring method for many years, they have paid little attention to how to best design and configure scoring tools. We explain how to design a scoring tool specifically tailored for a particular situation and present the example of Grundfos to illustrate the efficacy of developing a customized scoring method that includes identifying factors under Opportunity and Feasibility. We suggest how to choose the factors to ensure that the scoring is as consistent and objective as possible and how to treat the inevitable uncertainty arising from early-stage projects.